O języku i stylu poezji Jana Kasprowicza - Dzióbałtowska, Urszula (Acta Universitatis Lodziensis. Folia Linguistica, 1995)
The article contains a stylistic and linguistic analysis of Kasprowicz’s poems published in the period of Modernism. The following elements were selected from the texts of the poems: 1. deviations from the linguistic norm of the turn of the XIX and XX century, as well as potential variants of this norm; 2. phenomena remaining within the norm, but, e.g., typical of the period in question or of a given text. The selection comprised the following elements: phenomena considered then as rare, archaisms , dialectal phrases , localismus and neologismus . They were all described in chapters on phonetics , morphology , syntax and vocabulary . The kind of the elements selected and the extent to which they permeat the texts point out to moderate dialectizing and slight archaizing of poetry. Moderate permeation with innovations is also present. All these devices were, in accordance with the tradition, introduced primarily by means of lexical phenomena. Most of the linguistic means used can be classified as traditional and known in literature. The quality of these means and the way they are used make it possible for Kasprowicz to be counted among poets using interesting language.